Keadilan Sosial di Indonesia Ditinjau dalam Perspektif Nurcholish Madjid - Hasanah, Huswatun; Hidayatulloh, Taufik (JURNAL ILMIAH FALSAFAH: Jurnal Kajian Filsafat, Teologi dan Humaniora, 2024)
Social justice is a form of aspiration within a country or religion. Achieving social justice is not an easy task and is often difficult to attain. In reality, the current state of society is perceived as not having achieved equitable justice, especially in economic, educational, employment, and other aspects. Nurcholish Madjid, as a religious and national thinker, is concerned with issues of life, including religion, nationalism, and social justice. It is therefore necessary to understand Nurcholish Madjid's thoughts on social justice in Indonesian society and what needs to be done to achieve a just life. The research method is conducted by collecting data related to the discussion taken from journals or articles related to social justice. The research found that the lives of people, especially in Indonesia, have not been evenly distributed in terms of economy, education, and employment. Therefore, there is a need for cooperation between society and the state to achieve a just life in nation-building. Fundamentally, the state plays a crucial role in ensuring social justice for its people. Social justice means the absence of differences or discrimination in living. Nurcholish Madjid also states that the role of youth is crucial in making changes in the present and future. Any form of discrimination, coercion, and others can disrupt the principles of community life. As religious communities, we should not only focus on worship but also on the social aspects of religion because every religion teaches goodness. Discrimination and other forms of differences will only divide society and make it increasingly difficult to achieve social justice.